2020
DOI: 10.1002/2211-5463.12977
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of cytochrome P450 1A1 enhances lipopolysaccharide‐induced acute lung injury in mice by targeting NF‐κB activation

Abstract: Li-xing Tian, Xin Tang, Jun-yu Zhu and Hua-ping Liang contributed equally to this manuscript

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…PDTC suppresses the role of NF-κB by inhibiting IκBα phosphorylation. 26 , 27 In HK2 cells, PDTC inhibited the decrease in PGC-1 α protein levels induced by rhTWEAK treatment ( Figure 7B ), indicating that the canonical NF-κB pathway participated in the mediation of the TWEAK-induced downregulation of PGC-1α expression.
Figure 7 PDTC attenuated TWEAK regulation of PGC-1α expression.
…”
Section: Resultsmentioning
confidence: 92%
“…PDTC suppresses the role of NF-κB by inhibiting IκBα phosphorylation. 26 , 27 In HK2 cells, PDTC inhibited the decrease in PGC-1 α protein levels induced by rhTWEAK treatment ( Figure 7B ), indicating that the canonical NF-κB pathway participated in the mediation of the TWEAK-induced downregulation of PGC-1α expression.
Figure 7 PDTC attenuated TWEAK regulation of PGC-1α expression.
…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have demonstrated that CYP1A1 expression is induced depending on the expression level of aryl hydrocarbon receptor in the NASH model and that treatment of HepG2 cells with oleic acid accelerates lipid peroxidation (Xia et al, 2019). In addition, CYP1A1 expression is induced by LPS-induced NF-κB activation, which contributes to lung tissue damage and inflammation (Tian et al, 2020). In contrast, the CYP4A family contributes to the ω hydroxylation of saturated straight-chain fatty acids (Johnston et al, 2011;Choi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…During ALI, various oxidases are activated through different pathways, contributing to oxidative stress. These oxidases include NO synthase (NOS) [165], Xanthine oxidase (XO) [166] and Cytochrome P450 (CYP) [167]. Since many oxidases are present in endothelial mitochondria, and mitochondria are the primary site of REDOX reactions, oxidative stress can lead to mitochondrial damage.…”
Section: Imbalance Of Oxidative Stressmentioning
confidence: 99%